Spatio-temporal distribution analysis of brand interest in social networks - Teixeira, Diana Von-Haff Lopes (2018)
Social Networks applications such as Facebook and Twitter became part of many people’s lives and are used daily by millions of users. In such platforms, users share their emotions, opinions, experiences, and thoughts. Twitter, in particular, is used to discuss diverse topics, including brands, their products and services. In this thesis, we analyse how brand interest is reflected on Twitter and how this platform can be used to monitor what people say about specific brands, as an indicator of brand interest. Brand interest can be defined as the level of interest one has in a brand, and the level of curiosity one has to learn more about a brand. For this work, the volume of tweets is used as a measure of brand interest. Our methodology is based on time, location, and the number of brand-related tweets to perform a spatio-temporal analysis. Additionally, we propose a framework for discovering latent patterns (topics) from a large dataset of grouped short messages to analyse brand interest, using Twitter as a data source. We applied a well-known Text Mining technique called Topic Modelling, which is an unsupervised learning technique used when dealing with text data, useful to uncover topics in a collection of documents. This technique provides a convenient way to retrieve information from unstructured text. Topic Modelling tasks have been applied to track events/trends and uncover topics in domains such as academic, public health, marketing, and so forth. The framework consists of training LDA (Latent Dirichlet Allocation) topic models on aggregated tweets, and then applying the model on different documents, also composed by grouped Twitter posts. Furthermore, we describe a set of pre-processing tasks that helped to improve the performance of topic models, enabling us to obtain a better output, thus performing a better analysis of it. The experiments demonstrated that Topic Modelling can successfully track people’s discussions on Social Networks even in massive datasets such as the one used in the current work, and capture those topics spiked by real-life events